2016
DOI: 10.4238/gmr.15027661
|View full text |Cite
|
Sign up to set email alerts
|

A single nucleotide polymorphism in the promoter region (rs10877887) of let-7 is associated with hepatocellular carcinoma in a Chinese population

Abstract: ABSTRACT. Hepatocellular carcinoma (HCC) is a complex polygenic disease whose development is dependent on many genetic factors. The let-7 family, an important and widely studied microRNA family, has been shown to play an important role in the initiation and progression of HCC. In this study, we examined the possible associations between single-nucleotide polymorphisms in the promoter region of the let-7 family (rs10877887) and the susceptibility and prognosis of HCC, using a case-control research model. Eighty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
1
4
1
Order By: Relevance
“…Our results came in agreement with a study done by Huang et al, 15 who reported that the polymorphism in the rs 10877887 showed no statistical significance with susceptibility to HCC in Chinese population. This study itself -like our study-came in contrast with a study done by Sui et al, 16 on the same Chinese population and reported that SNP in the rs10877887 in the promoter region of Let-7 are significantly associated with high risk to HCC compared to those with the wild TT type. Another study done by Xie et al, 17 found that hepatocellular carcinoma patients carrying the C allele of rs10877887 in the promotor region of let-7i had a significantly increased death risk compared to patients with the TT genotype.…”
Section: Resultscontrasting
confidence: 99%
“…Our results came in agreement with a study done by Huang et al, 15 who reported that the polymorphism in the rs 10877887 showed no statistical significance with susceptibility to HCC in Chinese population. This study itself -like our study-came in contrast with a study done by Sui et al, 16 on the same Chinese population and reported that SNP in the rs10877887 in the promoter region of Let-7 are significantly associated with high risk to HCC compared to those with the wild TT type. Another study done by Xie et al, 17 found that hepatocellular carcinoma patients carrying the C allele of rs10877887 in the promotor region of let-7i had a significantly increased death risk compared to patients with the TT genotype.…”
Section: Resultscontrasting
confidence: 99%
“…However, we did not find any difference of rs10877887 between cases and controls. Inconsistent with our result, SNP rs10877887 CT/CC genotypes were reported to be a risk factor for lung cancer [15] and hepatocellular carcinoma [20]. In contrast, a reduced risk of rs10877887 CT/CC genotypes was reported in patients with papillary thyroid carcinoma [12].…”
Section: Discussionsupporting
confidence: 81%
“…Both the SNPs were predicted to influence the binding affinity with transcription factors [13]. Given the potential function, the two SNPs were widely investigated in numerous human diseases, including papillary thyroid carcinoma [12], lung cancer [15], hepatocellular carcinoma [20], intracranial aneurysm [33], major depressive disorder [34], and ischemic stroke [35]. However, the relationship between the two SNPs with BC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al demonstrated that the let7a‐2 rs10877887 polymorphism might be associated with a lower risk of PTC and the rs13293512 polymorphism could be correlated with lymph node metastasis in patients with PTC . In addition, several reports have described the association between let‐7 family polymorphisms and different cancers, such as head and neck cancer, hepatocellular carcinoma, and lung cancer …”
Section: Discussionmentioning
confidence: 99%